A photocapacitor with high working voltage and energy density. Issue 8 (24th June 2019) - Gao, Kun; Ti, Dan; Zhang, Zhipan
Abstract : The carbon-supported graphene/PEDOT common electrode enables the fabrication of photocapacitors with high voltage and energy density. Abstract : Photocapacitors have emerged as promising self-sufficient energy devices that combine solar cells and supercapacitors for simultaneous energy conversion and storage. Despite significant improvements in their performance during the past few years, fabricating photocapacitors with high open-circuit voltage and energy density remains challenging. Herein, with the aid of a carbon-supported graphene/PEDOT common electrode and an ionic liquid electrolyte, we have successfully developed a photocapacitor that can deliver an unprecedented open-circuit voltage of up to 1.8 V (4.7 V for an array of three photocapacitors in series) and an outstanding energy density of 0.18 W h m −2, together with a high overall efficiency of 7.0%. The device also shows good stability and performance under intermittent or low intensity light illumination.